Pendekatan Blue Economy dan Pengembangan Potensi Perikanan Laut di Wilayah Pesisir Kota Jayapura - Mollet, Julius Ary; Titalessy, Pisi Bethania; Zulhendri, Zulhendri (Society, 2024)
This study investigates the application of the blue economy approach in enhancing the potential of marine fisheries in the coastal areas of Jayapura City, Papua Province, Indonesia. Drawing upon the city’s abundant marine biodiversity and strategic geographical location, the research aims to examine the socio-economic dynamics of Indigenous coastal communities, evaluate the integration of blue economy principles, and propose strategic frameworks for sustainable fisheries management. Data were collected from 111 respondents across four key coastal regions in Jayapura using descriptive statistical methods, profitability analysis, and SWOT analysis. The findings reveal substantial untapped potential of marine fisheries hindered by challenges such as limited product diversification, inadequate market accessibility, and environmental constraints. The study emphasizes the critical need for comprehensive policy integration, community capacity-building, and ecological preservation to achieve sustainable development. This research contributes to local economic policy discourse and provides replicable insights for implementing blue economy initiatives in similar coastal contexts.